The influence of heart failure high-fidelity simulation education based on NLN Jeffries simulation framework in the prelicensure nursing program: A quasi-experimental study - Tricia Nwokocha; Nancy Cowan Pinio; Yan Cao; Holly Wei; Satish Mahajan (Elsevier, 2023)
Objectives: To examine the influence of heart failure high-fidelity simulation education based on the National League for Nursing (NLN) Jeffries Simulation Framework in prelicensure nursing education. Methods: A heart failure high-fidelity simulation (HFHFS) education pilot project was carried out at Carrington College Sacramento. Twenty-three students participated in the study. This study used a quasi-experimental design. Students' Self-Efficacy, Satisfaction, and Knowledge in Heart Failure Clinical Knowledge were measured pre- and post-HFHFS education. Results: The results of the high-fidelity simulation education for heart failure showed that students achieved a mean score of 45.39 (SD = 7.88) in self-efficacy, 18.70 (SD = 3.38) in satisfaction, and 64.09 (SD = 10.86) in knowledge after the intervention. The paired-sample t-test significantly improved between the pre- and post-intervention scores (P < 0.001). The students highly rated self-efficacy, student satisfaction, and knowledge because of the positive impact on the teaching effectiveness of simulation design (i.e., objectives, problem-solving, student support, fidelity, debriefing) activity that included the application of quality safety education for nurses (QSEN) three competencies safety, patient-centered care, and teamwork and collaboration during nursing care for patients with acute heart failure. The teaching effectiveness of the heart failure high-fidelity simulation education is closely correlated with student satisfaction, self-efficacy, and improvement of participant knowledge in clinical nursing skills performance and critical thinking. Conclusion: A heart failure high-fidelity simulation education established upon the National League for Nursing (NLN) Jeffries framework enhanced student knowledge, satisfaction, self-efficacy, application of safety, patient-centered care, and teamwork and collaboration. Nurse educators should consider simulation planning to include the five simulation design characteristics, i.e., objectives, problem-solving, student support, fidelity, and debriefing, while integrating safety, patient-centered care, and teamwork and collaboration to bring about education effectiveness.